Using Technology to Shift Education Paradigms in Low-Resource Environments. Issue 1 (19th May 2014) - Calhoun, Elizabeth; Calhoun, Nathaniel
As innovative and exponential technologies make their way into development projects and humanitarian aid interventions, pioneers are just starting to codify and publish their best practices, for example UNICEF's Child-Friendly Technology Framework. Code Innovation designed and lead the Connecting Classrooms project over seven years, bringing technology and education innovations to secondary school students, out-of-school youth and young adults in eleven countries around sub-Saharan Africa. The majority of participants had never experienced being connected to the Internet and there were numerous and ongoing challenges. Using collaborative teaching methodologies and a group learning approach, the program brought young people and their teachers or adult facilitators through a blended learning curriculum around key issues of shared global concern. This paper seeks to expand on lessons learned from the program to make recommendations for others to get the greatest leverage out of technology-supported education initiatives. As there is relatively little research published around multi-year technology for education projects in developing countries to date, this article strives to offer some best practices and lessons learned that will guide similar initiatives in the future.